Application of Learning Technology as a Strategy for New School Principals to Gain Acceptance - Dwi Yani; Syamsul Hadi; Riska Pristiani (Postgraduate, University of Mataram, 2024)
This research aims to describe the use of learning technology as a strategy used by novice principals to gain acceptance in the elementary school environment by novice principals to increase their acceptance in elementary schools. Learning technology includes a variety of tools and platforms that can improve learning quality, administrative efficiency, collaboration with parents, and teacher professional development. By implementing learning technology, novice principals can demonstrate visionary leadership, increase student motivation and engagement, and strengthen relationships with all stakeholders. This research approach uses a qualitative descriptive method with data analysis through in-depth interviews and participant observation at three elementary schools in Mojokerto Regency, namely SDN Tanjungkenongo 2 Pacet, SDN Ketapanrame 2 Trawas, and SDN Pagerluyung 1 Gedeg. The main informant for this research was the school principal and was triangulated with teachers and the school committee. The research results show that the use of learning technology as an innovation by novice school principals has great potential to increase their acceptance in elementary schools. By implementing learning technology, school principals can demonstrate visionary leadership, increase administrative efficiency, support teacher professional development, increase collaboration with parents, and increase student motivation and engagement. These findings provide important insights for educational leaders to improve their leadership effectiveness.